Positive electrode active material for lithium secondary battery, method for preparing same, and lithium secondary battery comprising same

By using lithium transition metal oxide composed of single particles as the positive electrode active material of lithium secondary batteries, the problem that small-particle multi-particle active material is prone to cracks or gases in lithium secondary batteries is solved, and high electrode density and excellent electrochemical characteristics are achieved.

CN120113066APending Publication Date: 2025-06-06POSCO HLDG INC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380074218.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-21
Filing Date
2023-10-20
Publication Date
2025-06-06

AI Technical Summary

Technical Problem

The existing small-particle multi-particle active materials are prone to cracks or gases in lithium secondary batteries, resulting in deterioration of the battery, and at the same time, the electrochemical characteristics are reduced when calcined at high temperatures.

Method used

A lithium transition metal oxide composed of single particles is used as the positive electrode active material. The maximum electrode density value of the (001) plane is less than 20 and has an average particle size of 2 to 4 μm, and a small particle size active material is pulverized from top to bottom.

Benefits of technology

The structural stability and electrochemical characteristics of the positive electrode active material are improved, the side reaction with the electrolyte is reduced, the life of the battery is extended, and the safety is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120113066A_ABST
    Figure CN120113066A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material for a lithium secondary battery, the positive electrode active material being a lithium transition metal oxide containing nickel (Ni), the lithium transition metal oxide being composed of single particles, having an average particle diameter (D50) of 2 to 4 [mu] m, and having a maximum pole density value corresponding to a (001) plane of 20 or less in a Pole Figure obtained by electron backscatter diffraction analysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium secondary battery positive electrode active material and a preparation method thereof, and a lithium secondary battery comprising the positive electrode active material. More specifically, the present invention relates to a lithium secondary battery positive electrode active material composed of single particles, a preparation method thereof, and a lithium secondary battery comprising the positive electrode active material. Background Art

[0002] Carbon neutrality is becoming increasingly important to prevent fossil fuel depletion and global warming, and to achieve this goal, it is essential to develop renewable energy and electric vehicles to replace internal combustion engine vehicles. To achieve this goal, lithium-ion secondary batteries have begun to be used as energy storage devices, and various positive electrode active materials have been developed to achieve secondary batteries with higher energy density and stability.

[0003] In particular, nickel-based layered structure positive electrode active materials (LiNiO 2 ) is the most actively studied. Generally, this type of positive electrode active material has a secondary aggregate multi-particle morphology in which primary particles are aggregated together. However, since such aggregate multi-particles have a large specific surface area, there is a high risk of gas generation by side reactions with the electrolyte, and when lithium transition metal oxides are pressed into a high electrode density to achieve a high-density electrode, there is a problem of low structural stability, such as particle rupture causing volume changes during charging and discharging, which causes cracks in the particles. In order to solve this problem, people began to study bimodal active materials using large-particle multi-particle active materials and small-particle multi-particle active materials, but the small-particle multi-particle active material has a larger specific surface area than the large-particle multi-particle active material, which has a greater impact on battery degradation.

[0004] In order to solve this problem, single-particle positive active materials are being developed. However, in order to synthesize single-particle (discrete particle) positive active materials, it is necessary to bake at a higher temperature than multi-particle positive active materials, and the electrochemical characteristics of lithium secondary batteries are significantly reduced. Summary of the invention

[0005] Technical issues to be solved

[0006] On one hand, the present invention provides a small-size single-particle positive electrode active material, which is used to solve the problem of existing small-size multi-particle active materials that produce cracks or gas leading to battery degradation, and at the same time has excellent electrochemical properties.

[0007] Another aspect of the present invention provides a method for preparing a small-size single-particle positive electrode active material having the above advantages.

[0008] Another aspect of the present invention provides a lithium secondary battery comprising the positive electrode active material.

[0009] Technical Solution

[0010] One embodiment of the present invention provides a lithium secondary battery positive electrode active material, which is a lithium transition metal oxide containing nickel (Ni), wherein the lithium transition metal oxide consists of single particles, has an average particle size (D50) of 2 to 4 μm, and has a maximum pole density (Max poledensity) value corresponding to the (001) plane in a pole figure (Pole Figure) obtained by electron backscatter diffraction (EBSD) analysis of 20 or less.

[0011] The positive electrode active material may not be preferentially arranged on the (001) plane during EBSD image analysis.

[0012] The positive electrode active material may be derived from a positive electrode active material precursor having an average particle size (D50) of 5 to 15 μm.

[0013] The lithium transition metal oxide may be represented by Chemical Formula 1 below.

[0014] [Chemical formula 1]

[0015] Li a (Ni b Me 1-b ) 2

[0016] In the above chemical formula 1, 0.8≤a≤1.2, 0.6≤b≤0.99, and Me is Co, Mn, Al, Zr, Nb, B, P, La, Mg, Ta, Ti, W, Mo, Si, Ga, Zn, Ag, Sn, Bi, Au, Y, Ge, V, Cr, Fe or a combination thereof.

[0017] At this time, the b may be 0.8≤b≤0.99.

[0018] The positive electrode active material further includes a coating located on the surface of the lithium transition metal oxide, and the coating may include Co, Al, Ti, W, B, F, P, Mg, Ni, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, S, La, Ta, Ga, or a combination thereof.

[0019] Another embodiment of the present invention provides a method for preparing a positive electrode active material for a lithium secondary battery, which comprises: a step of forming a mixture comprising a positive electrode active material precursor containing nickel (Ni) and a lithium raw material; a step of forming a lithium transition metal oxide by roasting the mixture; and a step of forming a lithium transition metal oxide composed of single particles by crushing the lithium transition metal oxide, wherein the average particle size (D50) of the positive electrode active material precursor is greater than the average particle size (D50) of the positive electrode active material.

[0020] The pulverization may be performed until the (001) plane of the lithium transition metal oxide is pulverized.

[0021] The pulverizing may be performed at a rotation speed of 3000 to 3600 rpm.

[0022] The pulverization may be performed at a pulverization pressure of 1.4 bar or more.

[0023] The positive active material precursor may have an average particle size (D50) of 5 to 15 μm.

[0024] The positive electrode active material may have an average particle size (D50) of 2 to 4 μm.

[0025] The calcination may be performed at 830 to 870° C. for 5 to 15 hours.

[0026] In the step of forming the mixture, a doping raw material is also mixed. The doping raw material can be a compound containing one or more of Zr, Nb, Al, B, P, La, Mg, Ta, Ti, W, Mo, Si, Ga, Zn, Ag, Sn, Bi, Au, Y, Ge, V, Cr and Fe, or a combination thereof.

[0027] After the step of forming the lithium transition metal oxide composed of single particles, the method further includes mixing the lithium transition metal oxide composed of single particles with a coating raw material and then heat treating the mixture to form a coating. The coating raw material can be a compound containing one or more of Co, Al, Ti, W, B, F, P, Mg, Ni, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, S, La, Ta and Ga, or a combination thereof.

[0028] Still another embodiment of the present invention provides a positive electrode including the aforementioned positive electrode active material.

[0029] Still another embodiment of the present invention provides a lithium secondary battery including the aforementioned positive electrode.

[0030] Beneficial Effects

[0031] The positive electrode active material according to one embodiment of the present invention is composed of single particles, so it has excellent structural stability and can achieve high electrode density. Not only because the side reactions with the electrolyte are reduced, the life and safety are excellent, but also because the electrochemically inactive surface (001) in the nickel-based layered structure is reduced, and the electrochemical characteristics such as capacity are excellent.

[0032] According to another embodiment of the present invention, the preparation method of the positive electrode active material adopts a top-down method using a medium-sized or large-sized precursor, which can reduce the (001) surface of the single-particle positive electrode active material. In addition, by using a medium-sized or large-sized precursor, the filling amount of the mixed product before calcination can be increased, thereby improving the productivity of the active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 EBSD images and pole figures of the positive electrode active materials prepared according to Example 1 and Comparative Example 1 are shown.

[0034] Figure 2 Scanning electron microscope (SEM) images of the positive electrode active materials prepared according to Example 1 and Comparative Example 1 are shown.

[0035] Figure 3 The capacity characteristic evaluation results of the lithium secondary batteries prepared according to Example 1 and Comparative Example 1 are shown.

[0036] Figure 4 High temperature life characteristics of lithium secondary batteries prepared according to Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0037] The words first, second, third, etc. are used to describe various parts, components, regions, layers and / or segments, but these parts, components, regions, layers and / or segments should not be limited by these words. These words are only used to distinguish a certain part, component, region, layer and / or segment from another part, component, region, layer and / or segment. Therefore, without departing from the scope of the present invention, the first part, component, region, layer and / or segment described below can also be described as the second part, component, region, layer and / or segment.

[0038] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. Unless the context otherwise clearly indicates the opposite, the singular form used is also intended to include the plural form. It should also be understood that the term "comprising" used in the specification may specifically refer to a certain characteristic, field, integer, step, action, element and / or component, but does not exclude the existence or addition of other characteristics, fields, integers, steps, actions, elements and / or components.

[0039] If a part is described as being on another part, the other part may be directly on the other part or there may be another part therebetween. If a part is described as being directly on another part, no other part may be therebetween.

[0040] Although not otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. Terms defined in dictionaries should be interpreted as having the same meaning as that disclosed in the relevant technical literature and this article, and should not be interpreted in an idealized or overly formal sense.

[0041] In addition, unless otherwise specified, % means weight %, and 1 ppm means 0.0001 weight %.

[0042] In the present specification, "a combination thereof" described in the Markush form expression refers to a mixture or combination of one or more selected from the group consisting of the constituent elements described in the Markush form expression, and means that one or more selected from the group consisting of the above constituent elements are included.

[0043] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various ways and is not limited to the embodiments described herein.

[0044] 1. Positive electrode active material

[0045] One embodiment of the present invention provides a lithium secondary battery positive electrode active material, which is a lithium transition metal oxide containing nickel (Ni), wherein the lithium transition metal oxide consists of single particles, has an average particle size (D50) of 2 to 4 μm, and has a maximum pole density (Max poledensity) value corresponding to the (001) plane in a pole figure (Pole Figure) obtained by electron backscatter diffraction (EBSD) analysis of 20 or less.

[0046] A lithium secondary battery positive electrode active material according to one embodiment of the present invention consists of a single particle.

[0047] More specifically, the positive electrode active material can be classified into ungranulated primary particles or secondary particles formed by granulating a plurality of primary particles, depending on whether the primary particles as unit particles are granulated or not. In this case, the positive electrode active material according to the present invention is composed of ungranulated primary particles, i.e., single particles.

[0048] Since the positive electrode active material is composed of a single particle as mentioned above, the following problems of secondary particles can be solved: due to the large specific surface area, the risk of side reactions with the electrolyte is high, the battery safety is reduced, and in order to achieve a high-density electrode, when the lithium transition metal oxide is pressed into a high electrode density, with repeated charging and discharging, fine cracks are generated between the primary particles, resulting in reduced structural stability and deterioration of life characteristics.

[0049] In addition, according to the single-particle positive electrode active material of the present invention, the average particle diameter (D50) thereof is 2 to 4 μm.

[0050] In this specification, the average particle size (D50) can be defined as the particle size corresponding to 50% of the volume cumulative amount in the particle size distribution curve of the particles. The average particle size (D50) can be measured, for example, using a laser diffraction method. The laser diffraction method can generally measure particle sizes ranging from submicron to several millimeters, and can achieve high reproducibility and high decomposition.

[0051] The particle size in the above range is suitable for small-particle active materials, and is particularly suitable for use as a small-particle active material mixed with a large-particle active material when preparing a bimodal positive electrode active material for realizing a high-density electrode.

[0052] However, generally, when single-particle positive electrode active materials are calcined at a higher temperature than multi-particle positive electrode active materials, the growth of the stable plane, i.e., the (001) plane, is dominant, and the particle morphology is elongated to the left and right. However, since the (001) plane is the plane that becomes the migration path of lithium ions, when the growth of the (001) plane is dominant, the migration distance of lithium ions becomes longer, and the electrochemical characteristics of the battery, such as capacity, initial efficiency, and high-temperature life characteristics, may deteriorate.

[0053] In order to solve the above problems, according to the positive electrode active material of the present invention, the growth of its (001) plane is suppressed, so that the maximum pole density (Max pole density) value corresponding to the (001) plane in the pole figure (Pole Figure) obtained by electron backscatter diffraction (EBSD) analysis is less than 20.

[0054] The maximum pole density value corresponding to the (001) plane in the pole figure obtained by EBSD analysis is a measure of the growth degree of the (001) plane. Since the range is met, the diffusion distance of lithium ions is reduced, and the degradation of the electrochemical characteristics of the battery can be minimized. For such growth inhibition of the (001) plane, it can be achieved by using a top-down method of a medium-sized or large-sized active material precursor, as described below. This will be described in detail later.

[0055] In this specification, the maximum pole density value corresponding to the (001) plane in the pole figure obtained by EBSD analysis refers to the value measured under the conditions of a step size of 50nm in an area of ​​20x50um using Hitachi's SU5000 as a FESEM image observation device and EDAX's Velocity Super as an EBSD data analysis device.

[0056] More specifically, the maximum pole density value may be 10 or more and 18 or 15 or less.

[0057] On the other hand, according to the positive electrode active material of one embodiment of the present invention, when measuring the X-ray diffraction pattern, the ratio of the peak intensity of the (003) plane to the peak intensity of the (104) plane I(003) / I(104) can be 1.4 or less, and more specifically can be 1.3 or less.

[0058] Generally, a peak intensity value refers to an integrated area value obtained by integrating a peak height value or a peak area. In the present specification, a peak intensity value refers to a peak area value.

[0059] The value is also a measure of the growth degree of the (001) plane. According to the positive electrode active material of one embodiment of the present invention, the growth of the (001) plane is suppressed, and the I(003) corresponding to the XRD peak of the (001) plane becomes relatively smaller than I(104), and I(003) / I(104) can be small enough to be below 1.4.

[0060] Therefore, the positive electrode active material according to the present invention may not be preferentially arranged on the (001) plane during EBSD image analysis.

[0061] The positive electrode active material may be derived from a positive electrode active material precursor having an average particle size (D50) of 5 to 15 μm. In other words, the positive electrode active material according to the present invention may be a small particle size active material prepared from a medium particle size or large particle size active material precursor using a top-down method, as described below.

[0062] The lithium transition metal oxide may be represented by the following Chemical Formula 1.

[0063] [Chemical formula 1]

[0064] Li a (Ni b Me 1-b ) 2

[0065] In the above chemical formula 1, 0.8≤a≤1.2, 0.6≤b≤0.99, and Me is Co, Mn, Al, Zr, Nb, B, P, La, Mg, Ta, Ti, W, Mo, Si, Ga, Zn, Ag, Sn, Bi, Au, Y, Ge, V, Cr, Fe or a combination thereof.

[0066] The a represents the molar ratio of lithium in the lithium transition metal oxide, and may be 0.8≤a≤1.2, 0.85≤a≤1.15 or 0.9≤a≤1.1.

[0067] The b represents the molar ratio of nickel to the total molar number of transition metals in the lithium transition metal oxide, which can be 0.60≤b≤0.99, 0.70≤b≤0.99, 0.80≤b≤0.99, 0.85≤b≤0.99, 0.90≤b≤0.99 or 0.90≤b≤0.95. When the nickel content in the lithium transition metal oxide meets the above range, a positive electrode active material and a lithium secondary battery with high capacity characteristics can be prepared.

[0068] In particular, b may be 0.8≤b≤0.99. In other words, the positive electrode active material according to the present invention is a high-nickel material having a nickel content of 80 mol % or more based on the total molar number of transition metals, and can achieve high capacity.

[0069] The positive electrode active material further comprises a coating on the surface of the lithium transition metal oxide, and the coating may comprise Co, Al, Ti, W, B, F, P, Mg, Ni, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, S, La, Ta, Ga or a combination thereof. By means of such a coating, the residual lithium present on the surface of the active material can be reduced, and the structural and chemical stability of the active material can be further improved.

[0070] Preferably, the coating may contain Co and Al.

[0071] The coating may have a thickness of 1 nm to 100 nm.

[0072] 2. Preparation method of positive electrode active material

[0073] Another embodiment of the present invention provides a method for preparing a positive electrode active material for a lithium secondary battery, which comprises: a step of forming a mixture comprising a positive electrode active material precursor containing nickel (Ni) and a lithium raw material; a step of forming a lithium transition metal oxide by roasting the mixture; and a step of forming a lithium transition metal oxide composed of single particles by crushing the lithium transition metal oxide, wherein the average particle size (D50) of the positive electrode active material precursor is greater than the average particle size (D50) of the positive electrode active material.

[0074] Hereinafter, a method for preparing a positive electrode active material according to another embodiment of the present invention will be described in detail according to each step.

[0075] First, a mixture including a positive electrode active material precursor containing nickel (Ni) and a lithium raw material material is formed.

[0076] More specifically, the positive electrode active material precursor may be a hydroxide containing nickel and manganese. Such a positive electrode active material precursor may be represented by the following Chemical Formula 2.

[0077] [Chemical formula 2]

[0078] Ni x2 Co y2 Mn z2 (OH) 2

[0079] In the above chemical formula 1,

[0080] 0.6≤x2≤0.99,0≤y2≤0.3,0 <z2≤0.3,x2+y2+z2=1。

[0081] The x2 represents the molar ratio of nickel in the total metal elements in the transition metal hydroxide, which can be 0.6≤x2≤0.99, 0.7≤x2≤0.99, 0.80≤x2≤0.99, 0.85≤x2≤0.99, 0.90≤x2≤0.99 or 0.90≤x2≤0.95. When the nickel content in the transition metal hydroxide meets the range, a positive electrode active material and a lithium secondary battery with high capacity characteristics can be prepared.

[0082] The y2 represents the molar ratio of cobalt in the total metal elements in the transition metal hydroxide, which can be 0≤y2≤0.3, 0.01≤y2≤0.2, 0.01≤y2≤0.1, 0.02≤y2≤0.08 or 0.02≤y2≤0.06.

[0083] The z2 represents the molar ratio of manganese in the total metal elements of the transition metal hydroxide, and it can be 0 < z2 ≤ 0.3, 0.01 ≤ z2 ≤ 0.2, 0.01 ≤ z2 ≤ 0.1, 0.02 ≤ z2 ≤ 0.08 or 0.02 ≤ z2 ≤ 0.06.

[0084] In particular, the average particle size (D50) of the precursor of the positive electrode active material can be 5 to 15 μm.

[0085] More specifically, the existing preparation method of single-particle positive electrode active material adopts the bottom-up method, and uses small-particle-size active material precursors to grow the particles to the required size through the calcination process. However, for such a preparation method, in the calcination process of increasing the particle size, the growth of the electrochemically stable (001) plane is dominant, and there is a problem of deterioration of the electrochemical properties of the secondary battery. Therefore, in the present invention, after calcining with medium-particle-size or large-particle-size precursors with an average particle size (D50) of 5 to 15 μm, random pulverization of the active material plane is carried out through the following pulverization process, so that a positive electrode active material with a reduced degree of preference of the (001) plane compared with the existing bottom-up method can be prepared. Moreover, by using medium-particle-size or large-particle-size precursors, the filling amount of the mixed product before calcination can be increased, thereby improving the productivity of the active material.

[0086] The lithium raw material substance can be lithium sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, hydroxyoxide, etc., and there is no particular limitation as long as it is soluble in water. Specifically, the lithium raw material substance can be Li 2 CO 3 、LiNO 3 、LiNO 2 、LiOH、LiOH·H2O、LiH、LiF、LiCl、LiBr、LiI、CH 3 COOLi、C 2 H 3 LiO 2 、Li 2 O、Li 2 O 2 、Li 2 SO 4 、Li 2 SO 3 、Li 3 C 6 H 5 O 7 or a combination thereof, but not limited thereto.

[0087] In the step of forming the mixture, a doping raw material may be mixed. In this case, the doping raw material may be a compound containing one or more of Zr, Nb, Al, B, P, La, Mg, Ta, Ti, W, Mo, Si, Ga, Zn, Ag, Sn, Bi, Au, Y, Ge, V, Cr and Fe, or a combination thereof.

[0088] Next, the mixture is calcined to form a lithium transition metal oxide.

[0089] The calcination forms a lithium transition metal oxide in which both primary particles and secondary particles formed by aggregation of the primary particles are present and single particles and multiple particles are mixed.

[0090] The calcination may be performed at a temperature of 830 to 870° C. If the calcination temperature is too low, the primary particles are too small, and problems such as gas generation or poor life may occur, while if the calcination temperature is too high, problems such as reduced capacity and efficiency due to excessive growth, cation mixing of Ni ions migrating to Li sites, etc. may occur.

[0091] The calcination may be performed for 5 to 15 hours, more specifically 8 to 12 hours or 9 to 11 hours. As with the temperature, if the calcination time is too short, the crystallinity is reduced and growth does not occur sufficiently, and problems such as gas generation or poor life may occur, while if the calcination time is too long, problems such as reduced capacity and efficiency due to excessive growth, cation mixing, etc. may occur.

[0092] The calcination can be performed in an oxygen environment. When a high-concentration nickel (Ni-rich) positive electrode active material with a high Ni content is calcined at a high temperature for a long time, Ni in the layered crystal structure occurs during the calcination process. 2+ Therefore, in order to prevent this, it is preferred to synthesize the positive electrode active material in an oxygen environment.

[0093] The calcination may be performed twice, that is, a primary calcination and a secondary calcination, as required. The secondary calcination allows the primary calcined product to be recrystallized, thereby forming a lithium transition metal oxide having a more excellent structural stability.

[0094] Next, the lithium transition metal oxide is pulverized to form a lithium transition metal oxide consisting of single particles. At this time, the pulverization may be performed until the (001) plane of the lithium transition metal oxide is pulverized.

[0095] More specifically, by the pulverization, the aggregation of the lithium transition metal oxide in the form of multiple particles of secondary particles in which the primary particles are aggregated is dispersed, and the lithium transition metal oxide consisting of only single particles can be formed.

[0096] In addition, by pulverizing at an appropriate rotation speed and pulverizing pressure, a transition metal oxide with a small particle size can be formed. In particular, by pulverizing at an appropriate rotation speed and pulverizing pressure, random active material surfaces are pulverized as described above, and a positive electrode active material with a reduced (001) surface can be formed.

[0097] More specifically, the pulverization may be performed at a rotation speed of 3000 to 3600 rpm. Since the rotation speed satisfies the above range, a small-sized active material having an appropriate size may be formed, and the (001) plane of the active material may be effectively reduced.

[0098] In addition, the pulverization can be performed at a pulverization pressure of 1.4 bar or more, more specifically, at a pulverization pressure of 1.4 bar or more, and 2 bar or less than 1.8 bar. Since the pulverization pressure meets the above range, a small particle size active material with an appropriate size can be formed, and the (001) plane of the active material can be effectively reduced.

[0099] The pulverization method is not particularly limited and can be carried out according to conventional pulverization methods in the art. For example, a jet-mill process can be used.

[0100] Through such a pulverization process, a small-particle positive electrode active material consisting of single particles, having an average particle size (D50) of 2 to 4 μm and in which growth of the (001) plane is suppressed can be obtained.

[0101] After the step of forming the lithium transition metal oxide consisting of single particles, the method may further include mixing the lithium transition metal oxide consisting of single particles with a coating material and then heat treating the mixture to form a coating.

[0102] At this time, the coating raw material can be a compound containing one or more of Co, Al, Ti, W, B, F, P, Mg, Ni, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, S, La, Ta and Ga, or a combination thereof.

[0103] More specifically, the coating raw material may include Co 3 O 4 and Al(OH) 3 .

[0104] At this time, the coating material may be present in an amount of 1 to 5 wt %, more specifically 1.5 to 3 wt %, based on the total weight of the lithium transition metal oxide. If the coating material is present in an amount too little, the electrochemical capacity and lifespan may be deteriorated due to residual lithium present on the surface, while if the coating material is present in an amount too much, the surface resistance may be increased, resulting in reduced capacity and efficiency.

[0105] The heat treatment may be performed at a temperature of 550 to 800°C, and more specifically, may be performed at a temperature of 600 to 750°C or 650 to 700°C.

[0106] The heat treatment may be performed for 2 to 10 hours, more specifically, for 3 to 7 hours or 4 to 6 hours.

[0107] Since the heat treatment temperature and the heat treatment time satisfy the above ranges, residual lithium is suppressed and a uniform surface coating can be obtained.

[0108] 3. Positive electrode

[0109] Still another embodiment of the present invention provides a positive electrode including the aforementioned positive electrode active material.

[0110] The positive electrode may include a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer may include the positive electrode active material described above.

[0111] There is no particular limitation on the positive electrode collector as long as it does not cause chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 to 500 μm, and fine concavoconvexities can be formed on the surface of the positive electrode collector to improve the adhesion of the positive electrode active material. For example, various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc. can be used.

[0112] The positive electrode active material layer may optionally include a binder and / or a conductive material together with the aforementioned positive electrode active material.

[0113] The binder plays a role in improving the adhesion between the positive electrode active material particles and the bonding force between the positive electrode active material and the positive electrode collector. As a specific example, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., of which one can be used alone or a mixture of two or more can be used, but is not limited thereto. Relative to the total weight of the positive electrode active material layer, the binder may include 1 to 30 weight %.

[0114] The conductive material is used to impart conductivity to the electrode, and the conductive material can be used without restriction as long as it does not cause chemical changes in the composed battery and has electronic conductivity. As specific examples, graphite such as natural graphite or artificial graphite, etc.; carbon-based substances such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, carbon fiber, etc.; metal powder or metal fiber such as copper, nickel, aluminum, silver, etc.; conductive whiskers such as zinc oxide, potassium titanate, etc.; conductive metal oxides such as titanium oxide, etc.; or conductive polymers such as polyphenylene derivatives, etc., of which one can be used alone or a mixture of two or more can be used, but it is not limited thereto. Generally, the conductive material can contain 1 to 30 weight % relative to the total weight of the positive electrode active material layer.

[0115] The positive electrode can be prepared according to a conventional positive electrode preparation method.

[0116] Specifically, a positive electrode active material layer-forming composition comprising a positive electrode active material and an optional binder, a conductive material or a solvent as required is applied to a positive electrode current collector, and then dried and pressed, thereby preparing the positive electrode. At this time, the types and contents of the positive electrode active material, the binder and the conductive material are as described above.

[0117] The solvent may be a solvent generally used in the technical field, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, etc., of which one may be used alone or a mixture of two or more. The amount of the solvent used, considering the coating thickness and preparation yield of the slurry, as long as it has a certain viscosity, it is sufficient to dissolve or disperse the positive electrode active material, the conductive material and the binder, and then can show excellent thickness uniformity when coating the positive electrode.

[0118] In addition, as another method, the positive electrode can also be produced by casting the positive electrode active material layer-forming composition on a separate support and then laminating a film obtained by peeling off the support on a positive electrode collector.

[0119] 4. Lithium secondary battery

[0120] Still another embodiment of the present invention provides a lithium secondary battery including the aforementioned positive electrode.

[0121] In particular, the lithium secondary battery according to the present invention may have an initial charge capacity of 228 mAh / g or 229 mAh / g or more, an initial discharge capacity of 205 mAh / g or 206 mAh / g or more, and an initial efficiency of 90% or more.

[0122] In addition, according to the lithium secondary battery of the present invention, the high temperature life retention rate can be 91.3% or more, and the high temperature resistance increase rate can be 169% or less.

[0123] More specifically, the lithium secondary battery may include: the aforementioned positive electrode; a negative electrode located opposite to the positive electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.

[0124] In addition, the lithium secondary battery may optionally further include a battery container accommodating an electrode assembly of a positive electrode, a negative electrode, and a separator, and a sealing member sealing the battery container.

[0125] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector.

[0126] There is no particular limitation on the negative electrode current collector as long as it does not cause chemical changes in the battery and has conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can generally have a thickness of 3 to 500 μm. Like the positive electrode current collector, fine concave-convex can also be formed on the surface of the current collector to strengthen the binding force of the negative electrode active material. For example, various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc. can be used.

[0127] The negative electrode active material layer may optionally contain a binder and a conductive material together with the negative electrode active material. As an example, the negative electrode active material layer may be prepared by coating a negative electrode active material layer-forming composition containing a negative electrode active material and optional binder and conductive material on a negative electrode current collector and drying, or by casting the negative electrode forming composition onto a separate support, and then laminating the film obtained by peeling off the support onto the negative electrode current collector.

[0128] As the negative electrode active material, a compound capable of reversibly inserting and deinserting lithium can be used. As specific examples, carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, etc.; metal compounds that can form alloys with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy or Al alloy, etc.; metal oxides that can dope and dedope lithium such as SiO β (0<β<2), SnO 2 , vanadium oxide, lithium vanadium oxide; or a composite containing the metal compound and a carbon material such as a Si-C composite or a Sn-C composite, any one of which or a mixture of two or more thereof can be used. In addition, as the negative electrode active material, a metallic lithium film can also be used. In addition, for carbon materials, both low-crystalline carbon and high-crystalline carbon can be used. Typical low-crystalline carbons are soft carbon and hard carbon, and typical high-crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesophase carbon microbeads, mesophase pitches, and high-temperature sintered carbons such as petroleum or coal tar pitch derived cokes.

[0129] The binder and the conductive material may be the same as those of the aforementioned positive electrode.

[0130] The diaphragm is used to isolate the negative electrode and the positive electrode and to provide a migration channel for lithium ions. As long as it is used as a diaphragm in a lithium secondary battery, there is no particular restriction. In particular, it is preferred to use a diaphragm with low ion migration resistance to the electrolyte and excellent electrolyte wettability. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of more than two layers thereof. In addition, conventional porous non-woven fabrics can also be used, for example, non-woven fabrics made of high melting point glass fibers, polyethylene terephthalate fibers, etc. In addition, in order to ensure heat resistance or mechanical strength, a diaphragm after coating containing a ceramic component or a polymer material can also be used, and a monolayer or multilayer structure can be optionally used.

[0131] As the electrolyte, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc. that can be used when preparing lithium secondary batteries can be cited, but are not limited thereto.

[0132] Specifically, the organic liquid electrolyte may include an organic solvent and a lithium salt.

[0133] As the organic solvent, any solvent that can play the role of a medium for the migration of ions participating in the electrochemical reaction of the battery can be used without special restrictions. Specifically, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran, etc.; ketone solvents such as cyclohexanone, etc.; aromatic hydrocarbon solvents such as benzene, fluorobenzene, etc.; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (propylene carbonate, etc.) can be used. carbonate, PC), etc.; alcohol solvents such as ethanol, isopropanol, etc.; nitriles such as R-CN (R is a straight chain, branched or cyclic hydrocarbon group from C2 to C20, which may contain a double bond aromatic ring or an ether bond), etc.; amides such as dimethylformamide, etc.; dioxolanes such as 1,3-dioxolane, etc.; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate, etc.) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery and low viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be exhibited.

[0134] As for the lithium salt, any compound that can provide lithium ions used in lithium secondary batteries can be used without particular limitation. Specifically, the lithium salt can be LiPF 6 、LiClO 4 、LiAsF6 , LiBF 4 、LiSbF 6 、LiAl0 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 .LiCl, LiI or LiB(C 2 O 4 ) 2 The concentration of the lithium salt is preferably in the range of 0.1 to 2.0 M. If the concentration of the lithium salt falls within the range, the electrolyte has appropriate conductivity and viscosity, and thus can exhibit excellent electrolyte performance, and lithium ions can be efficiently transferred.

[0135] In addition to the electrolyte components, in order to improve battery life characteristics, inhibit battery capacity reduction, improve battery discharge capacity, etc., the electrolyte may also include one or more halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N, N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol or aluminum chloride and other additives. At this time, relative to the total weight of the electrolyte, the additive may include 0.1 to 5 weight %.

[0136] Hereinafter, the embodiments of the present invention will be described in further detail by way of examples. However, the following examples are only preferred embodiments of the present invention, and the present invention is not limited to the following examples.

[0137] Example 1: Preparation of positive electrode active material by top-down method

[0138] (1) Preparation of positive electrode active materials

[0139] 275 g of an average particle size (D50) of 15 μm and a composition of (Ni 0.88 Co 0.04 Mn 0.08)(OH) 2 of active material precursor, 125 g of LiOH·H 2 O, 0.729 g ZrO 2 Add to a mixer and form a mixture by mechanical mixing.

[0140] Then, the mixture was calcined at 850° C. for 10 hours in an oxygen environment to form a lithium transition metal oxide.

[0141] Then, in order to disperse the aggregation of the lithium transition metal oxide and adjust the particle size of the active material, the lithium transition metal oxide is pulverized by a jet mill process to form a lithium transition metal oxide composed of single particles. At this time, the pulverization is carried out under the conditions of a pulverization pressure of 1.5 bar and a rotation speed of 3300 rpm.

[0142] Then, 0.172 g of LiOH·H was mixed with 40 g of the obtained lithium transition metal oxide. 2 O, 0.533 g of Co 3 O 4 , 0.162 g of Al(OH) 3 Then, heat treatment was performed at 650-700°C for 5 hours.

[0143] Finally, LiNi 0.88 Co 0.04 Mn 0.08 Zr 0.002 The surface of the lithium transition metal oxide is coated with a single particle positive electrode active material of 1 mol % Li, 5 mol % Co, and 0.5 mol % Al.

[0144] (2) Preparation of lithium secondary batteries

[0145] A coin half-cell lithium secondary battery is prepared using the positive electrode active material prepared by the method.

[0146] The slurry for preparing the plate is positive electrode active material: conductive material (acetylene black): binder (PVDF, KF1120) = 96.5:1.5:2wt%, and NMP (N-methyl-2-pyrrolidone) is added for solid content and slurry viscosity. The prepared slurry is coated on aluminum foil (Al foil) with a doctor blade, and pressed after drying to prepare the plate. At this time, the electrode loading is 15-16 mg / cm 2 , the mixed density of the electrode is 3.5g / cm 3 above.

[0147] The electrolyte used in the coin cell is 1M LiPF6 in EC:DMC:EMC=3:4:3 (vol%)+VC3.0wt%, and a PP separator and a lithium negative electrode (300μm) are used to make a coin half-cell.

[0148] Comparative Example 1: Preparation of positive electrode active material by bottom-up method

[0149] The average particle size (D50) was 3.5 μm and the composition was (Ni 0.88 Co 0.04 Mn 0.08 )(OH) 2 The active material precursor was pulverized under the conditions of a pulverizing pressure of 1.3 bar and a rotation speed of 3300 rpm. Except for this, a positive electrode active material and a lithium secondary battery were prepared by the same embodiment as in Example 1.

[0150] Table 1 below summarizes the process conditions and physical properties of the positive electrode active materials according to Experimental Examples 1 and 2 below.

[0151]

Table 1

[0152]

[0153] Experimental Example 1: EBSD Analysis of Positive Electrode Active Materials

[0154] EBSD images of the positive electrode active materials prepared according to Example 1 and Comparative Example 1 ( Figure 1 ) and the pole figure (Pole Figure) of the (001) plane direction obtained by EBSD analysis ( Figure 1 The maximum pole density of the (001) surface is analyzed below. The results are shown in Figure 1 and Table 1. The specific measurement method is as follows.

[0155] Hitachi's SU5000 was used as a FESEM image observation device, and EDAX's VelocitySuper was used as an EBSD data analysis device. The measurement was performed under the condition of a step size of 50 nm in an area of ​​20x50 um.

[0156] Reference Figure 1 The EBSD images of the positive electrode active material of Example 1 confirm that the growth of the (001) plane is suppressed and no preferential arrangement occurs on the (001) plane. On the other hand, the positive electrode active material of Comparative Example 1 has excessive growth on the (001) plane and preferential arrangement occurs on the (001) plane.

[0157] In addition, refer to Figure 1It can be confirmed from the pole figure that the maximum pole density value of the positive electrode active material according to Example 1 is 14.348, while the maximum pole density value of the positive electrode active material according to Comparative Example 1 is 29.022.

[0158] Experimental Example 2: Evaluation of the shape and average particle size (D50) of the positive electrode active material

[0159] The shapes of the positive electrode active materials prepared according to Example 1 and Comparative Example 1 were observed by scanning electron microscopy (SEM), and the results are shown in FIG. Figure 2 middle.

[0160] Reference Figure 2 It can be confirmed that the positive electrode active materials according to Example 1 and Comparative Example 1 each have a single particle form composed of non-granulated primary particles.

[0161] In addition, the average particle size (D50) of the positive electrode active material according to Example 1 was about 3.00 μm, and the average particle size (D50) of the positive electrode active material according to Comparative Example 1 was about 3.56 μm.

[0162] Experimental Example 3: Evaluation of electrochemical characteristics of lithium secondary batteries

[0163] Electrochemical characteristics evaluation experiments were conducted on the lithium secondary batteries prepared according to Example 1 and Comparative Example 1. The specific experimental methods are as follows.

[0164] (1) Evaluation of initial capacity and initial efficiency

[0165] After making the lithium secondary battery, it was aged at room temperature for 10 hours and then subjected to charge and discharge tests. In order to evaluate the initial capacity, 200 mAh / g was used as the reference capacity, and it was charged to 4.25 V at a constant current of 0.1 C, and then switched to constant voltage charging until the end current reached 0.05 C.

[0166] After charging, the battery was left to rest for 20 minutes, and then discharged at a constant current of 0.1C with a reference capacity of 200 mAh / g until it reached 3.0V.

[0167] The results are shown in Figure 3 and Table 1 below.

[0168] (2) Evaluation of high temperature life characteristics

[0169] For high temperature life characteristics, the battery was charged and discharged 100 times at 45°C under the conditions of 0.5C charge and 1.0C discharge. The capacity retention rate and resistance increase rate of the 100 cycles relative to the first cycle were measured. The results are shown in Figure 4 and Table 2 below.

[0170]

Table 2

[0171]

[0172]

[0173] Reference Figure 3 It can be confirmed from Table 2 that the lithium secondary battery according to Example 1 is superior to the lithium secondary battery according to Comparative Example 1 in terms of initial charge capacity, discharge capacity, and initial efficiency. Figure 4 It can be confirmed from Table 2 that the lithium secondary battery according to Example 1 has a higher high temperature life retention rate and a lower high temperature resistance increase rate than the lithium secondary battery according to Comparative Example 1, and has excellent high temperature life characteristics.

[0174] This is because the positive electrode active material according to Example 1 is composed of a single particle, and since the (001) plane is reduced, the capacity, initial efficiency, and high-temperature life characteristics of the battery are improved.

[0175] Although the preferred embodiments of the present invention are described above, the present invention is not limited thereto, and various modifications can be made within the scope of the claims, the specification, and the drawings, and these modifications also fall within the scope of the present invention.

[0176] Therefore, the true scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A positive electrode active material for a lithium secondary battery, which is a nickel-containing lithium transition metal oxide, wherein the lithium transition metal oxide is composed of single particles, has an average particle size (D50) of 2 to 4 μm, and has a maximum pole density value of less than 20 corresponding to the (001) plane in the pole figure obtained by electron backscatter diffraction analysis.

2. The positive electrode active material for a lithium secondary battery according to claim 1, in, There is no preferential arrangement on the (001) plane during EBSD image analysis.

3. The positive electrode active material for a lithium secondary battery according to claim 1, in, The positive electrode active material is derived from a positive electrode active material precursor having an average particle size (D50) of 5 to 15 μm.

4. The positive electrode active material for a lithium secondary battery according to claim 1, in, The lithium transition metal oxide is represented by the following chemical formula 1: [Chemical formula 1] Li a (Ni b Along with 1-b )O 2 In the above chemical formula 1, 0.8≤a≤1.2, 0.6≤b≤0.99, and Me is Co, Mn, Al, Zr, Nb, B, P, La, Mg, Ta, Ti, W, Mo, Si, Ga, Zn, Ag, Sn, Bi, Au, Y, Ge, V, Cr, Fe or a combination thereof.

5. The positive electrode active material for a lithium secondary battery according to claim 4, in, 0.8≤b≤0.99。 6. The positive electrode active material for a lithium secondary battery according to claim 1, in, The positive electrode active material also includes a coating located on the surface of the lithium transition metal oxide, wherein the coating includes Co, Al, Ti, W, B, F, P, Mg, Ni, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, S, La, Ta, Ga or a combination thereof.

7. A method for preparing a positive electrode active material for a lithium secondary battery, comprising: a step of forming a mixture comprising a positive electrode active material precursor containing nickel and a lithium raw material material; A step of forming a lithium transition metal oxide by calcining the mixture; a step of forming a lithium transition metal oxide consisting of single particles by pulverizing the lithium transition metal oxide, The average particle size (D50) of the positive electrode active material precursor is larger than the average particle size (D50) of the positive electrode active material.

8. The method for preparing the positive electrode active material for a lithium secondary battery according to claim 7, in, The pulverization is performed until the (001) plane of the lithium transition metal oxide is pulverized.

9. The method for preparing the positive electrode active material for a lithium secondary battery according to claim 7, in, The pulverizing is performed at a rotation speed of 3000 to 3600 rpm.

10. The method for preparing the positive electrode active material for a lithium secondary battery according to claim 8, in, The pulverization is carried out at a pulverization pressure of 1.4 bar or more.

11. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 7, in, The average particle size (D50) of the positive electrode active material precursor is 5 to 15 μm.

12. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 7, in, The average particle size (D50) of the positive electrode active material is 2 to 4 μm.

13. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 7, in, The calcination is performed at a temperature of 830 to 870° C. for 5 to 15 hours.

14. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 7, in, In the step of forming a mixture, A doping raw material is also mixed, wherein the doping raw material is a compound containing one or more of Zr, Nb, Al, B, P, La, Mg, Ta, Ti, W, Mo, Si, Ga, Zn, Ag, Sn, Bi, Au, Y, Ge, V, Cr and Fe, or a combination thereof.

15. The method for preparing the positive electrode active material for lithium secondary battery according to claim 7, in, After the step of forming the lithium transition metal oxide consisting of single particles, The invention also comprises the step of mixing the lithium transition metal oxide composed of single particles and a coating raw material and then heat treating the mixture to form a coating, wherein the coating raw material is a compound containing one or more of Co, Al, Ti, W, B, F, P, Mg, Ni, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, S, La, Ta and Ga or a combination thereof. 16 . A positive electrode comprising the positive electrode active material according to claim 1 . 17 . A lithium secondary battery comprising the positive electrode according to claim 16 .